Chronic cervical radiculopathic pain is associated with increased excitability and hyperpolarization-activated current (Ih) in large-diameter dorsal root ganglion neurons. Issue 1 (June 2017) - Liu, Da-Lu; Wang, Xu; Chu, Wen-Guang; Lu, Na; Han, Wen-Juan; Du, Yi-Kang; Hu, San-Jue; Bai, Zhan-Tao; Wu, Sheng-Xi; Xie, Rou-Gang; Luo, Ceng
Cervical radiculopathic pain is a very common symptom that may occur with cervical spondylosis. Mechanical allodynia is often associated with cervical radiculopathic pain and is inadequately treated with current therapies. However, the precise mechanisms underlying cervical radiculopathic pain-associated mechanical allodynia have remained elusive. Compelling evidence from animal models suggests a role of large-diameter dorsal root ganglion neurons and plasticity of spinal circuitry attached with Aβ fibers in mediating neuropathic pain. Whether cervical radiculopathic pain condition induces plastic changes of large-diameter dorsal root ganglion neurons and what mechanisms underlie these changes are yet to be known. With combination of patch-clamp recording, immunohistochemical staining, as well as behavioral surveys, we demonstrated that upon chronic compression of C7/8 dorsal root ganglions, large-diameter cervical dorsal root ganglion neurons exhibited frequent spontaneous firing together with hyperexcitability. Quantitative analysis of hyperpolarization-activated cation current ( I h ) revealed that I h was greatly upregulated in large dorsal root ganglion neurons from cervical radiculopathic pain rats. This increased I h was supported by the enhanced expression of hyperpolarization-activated, cyclic nucleotide-modulated channels subunit 3 in large dorsal root ganglion neurons. Blockade of I h with selective antagonist, ZD7288 was able to eliminate the mechanical allodynia associated with cervical radiculopathic pain. This study sheds new light on the functional plasticity of a specific subset of large-diameter dorsal root ganglion neurons and reveals a novel mechanism that could underlie the mechanical allodynia associated with cervical radiculopathy.